Early assessment of forest growth in a logged over coastal lowland mixed dipterocarp forest in Bintulu, Sarawak, Malaysia - Ong, Kian Huat; Yong, Pei Li; Kueh, Roland Jui Heng (Universiti Malaysia Sarawak, 2024)
Managing regrowth forests sustainably is a necessary tactic to address climate change as these forests' ability to capture and sequester carbon is much higher due to their potential high growth rate. These forests also retained high tree diversity if subjected to selective logging previously. The objectives of this study were to investigate growth rate of tree species in a logged over coastal lowland mixed dipterocarp forest. This study was carried out in 10 established plots (50 m × 20 m) at a logged-over forest in Universiti Putra Malaysia Bintulu Sarawak Campus, Sarawak, Malaysia and trees with 10 cm diameter breast height (dbh) and above were measured. There were 611 individual trees of 159 species and 43 families were found in a one-hectare. The majority of trees (86%) were found in smaller diameter classes (<30 cm) with only 2% in diameter classes of more than 50 cm. The study area still retains a mixed dipterocarp forest feature. The stand has a good growth rate. Overall dbh increment was 0.34 cm yr-1 with dipterocarps documented 0.39 cm yr-1. A reverse growth dominance was observed in this study where smaller trees recorded higher growth. Thus contributing up to 72% of carbon sequestrated by this group of trees.